Morbidity and mortality of lobectomy or pneumonectomy after neoadjuvant treatment: an analysis from the ESTS database. (22nd October 2019) - Brunelli, Alessandro; Rocco, Gaetano; Szanto, Zalan; Thomas, Pascal; Falcoz, Pierre Emmanuel
Abstract: : OBJECTIVES: To evaluate the postoperative complications and 30-day mortality rates associated with neoadjuvant chemotherapy before major anatomic lung resections registered in the European Society of Thoracic Surgeons (ESTS) database. METHODS: Retrospective analysis on 52 982 anatomic lung resections registered in the ESTS database (July 2007–31 December 2017) (6587 pneumonectomies and 46 395 lobectomies); 5143 patients received neoadjuvant treatment (9.7%) (3993 chemotherapy alone and 1150 chemoradiotherapy). To adjust for possible confounders, a propensity case-matched analysis was performed. The postoperative outcomes (morbidity and 30-day mortality) of matched patients with and without induction treatment were compared. RESULTS: 8.2% of all patients undergoing lobectomies and 20% of all patients undergoing pneumonectomies received induction treatment. Lobectomy analysis: propensity score analysis yielded 3824 pairs of patients with and without induction treatment. The incidence of cardiopulmonary complications was higher in the neoadjuvant group (626 patients, 16% vs 446 patients, 12%, P < 0.001), but 30-day mortality rates were similar (71 patients, 1.9% vs 75 patients, 2.0%, P = 0.73). The incidence of bronchopleural fistula and prolonged air leak >5 days were similar between the 2 groups (neoadjuvant: 0.5% vs 0.4%, P = 0.87; 9.2% vs 9.9%, P = 0.27). Pneumonectomy analysis: propensity score analysis yielded 1312 pairs of patients with and without induction treatment. The incidence of cardiopulmonary complications was higher in the treated patients compared to those without neoadjuvant treatment (neoadjuvant 275 cases, 21% vs 18%, P = 0.030). However, the 30-day mortality was similar between the matched groups (neoadjuvant 68 cases, 5.2% vs 5.3%, P = 0.86). Finally, the incidence of bronchopleural fistula was also similar between the 2 groups (neoadjuvant 1.8% vs 1.4%, P = 0.44). CONCLUSIONS: Neoadjuvant chemotherapy is not associated with an increased perioperative risk after either lobectomy or pneumonectomy, warranting a more liberal use of this approach for patients with locally advanced operable lung cancer.